Estragole Ameliorates CFA Induced Rheumatoid Arthritis Symptoms in Wistar Rats by Inhibiting JAK-2/STAT-3 Pathway - Zhang, J; Wang, D; Hu, X (Physiological research, 2024)
The present study was conducted to scrutinize the pharmacological effect of Estragole (ESG) against CFA-induced arthritis in rats. The rats underwent induction of arthritis using the administration of CFA and after that, the rats were randomly divided into five different groups, where three groups correspond to diverse dosages of ESG, and the other two were control and CFA-arthritic control. Results of the study suggested that ESG in a dose-dependent manner, improves body weight and arthritis score of rats as evidenced by reduction of hind-paw volume. ESG also improved the antioxidant status of rats by reducing MDA levels and enhancing the concentration of endogenous antioxidants SOD and GPx. The level of pro-inflammatory cytokines was also found to be reduced in the case of ESG treated group as compared to CFA-group. In a western blot analysis, ESH showed downregulation of p-JAK-2/STAT-3. The study provided concrete evidence for the protective effect of ESG against rheumatoid arthritis in rats.
Keywords: potkani Wistar; cytokiny; Rats; revmatoidní artritida; allylbenzenové deriváty; antioxidancia; Animals; Anisoles; artritida experimentální; krysa rodu Rattus; Rats, Wistar; Allylbenzene Derivatives; anisoly; zvířata; Antioxidants; Arthritis, Experimental; Cytokines; Arthritis, Rheumatoid